2007
DOI: 10.1111/j.1095-8312.2007.00717.x
|View full text |Cite
|
Sign up to set email alerts
|

Reticulate evolution: ancient introgression of the Adriatic brown trout mtDNA in softmouth trout Salmo obtusirostris (Teleostei: Salmonidae)

Abstract: Two populations of softmouth trout (Salmo obtusirostris) from the rivers Neretva (Bosnia and Herzegovina) and Jadro (Croatia), along with two neighbouring populations of brown trout (Salmo trutta) were analysed with a suite of genetic markers (two mtDNA genes, two nuclear genes, and nine microsatellites) as well as morphological characters. The Jadro softmouth trout were fixed for a brown trout mtDNA haplotype of the Adriatic lineage, which is 1.7% divergent from a previously described haplotype characteristic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 56 publications
(55 reference statements)
2
36
0
2
Order By: Relevance
“…The greater genetic differentiation of BES_24, BED_7 and PEZ_E15 individuals, observed using D-loop, wasn't corroborated by the microsatellites. The differing phylogenetic signal has previously been observed in some fish species (Freyhof et al 2005;Sušnik et al 2007) and in mammals (Kingston et al 2009). Recently, Wang et al (2011) reported that the cross between a triploid male gibel carp and a gynogentic female clone resulted in a novel nucleocytoplasmic hybrid clone, where the nucleus came from the male, whereas the mtDNA came from the female; suggesting that the novel clone might have arisen via androgenesis by a mechanism of ploidy doubling of male sperm in female ooplasm.…”
Section: The Origin Of Croatian Cac Populationsmentioning
confidence: 80%
“…The greater genetic differentiation of BES_24, BED_7 and PEZ_E15 individuals, observed using D-loop, wasn't corroborated by the microsatellites. The differing phylogenetic signal has previously been observed in some fish species (Freyhof et al 2005;Sušnik et al 2007) and in mammals (Kingston et al 2009). Recently, Wang et al (2011) reported that the cross between a triploid male gibel carp and a gynogentic female clone resulted in a novel nucleocytoplasmic hybrid clone, where the nucleus came from the male, whereas the mtDNA came from the female; suggesting that the novel clone might have arisen via androgenesis by a mechanism of ploidy doubling of male sperm in female ooplasm.…”
Section: The Origin Of Croatian Cac Populationsmentioning
confidence: 80%
“…S5). We excluded wolf populations for which structure analysis suggested substantial admixture with coyotes (see above), as admixture would be expected to cause reticulation in relationship trees (Posada and Crandall 2001;Susnik et al 2007;Addison and Pogson 2009). Rooted with the coyote, Old and New World populations are the first division in the gray wolf tree (Supplemental Fig.…”
Section: Global Patterns Of Population Subdivisionmentioning
confidence: 99%
“…Fifteen microsatellites (BFRO002, Ssa197, Str591, Str24, BFRO001, Ssosl438, Str58, Str-LDH4, Onel2, Ssa410, Sssp2216, Ssa408, SsaD190, Omm1064, Sssp2213) were analysed. GenBank accession numbers, original references and PCR-protocols have been described elsewhere (Sušnik et al 2007;and Lerceteau-Kö hler and Weiss 2006).…”
Section: Samples and Microsatellite Setmentioning
confidence: 99%